Sport and crime: towards a critical criminology of sport - Millward, Peter (Frontiers of sport, 2023)
Introduction -- Sport and the critical criminological imagination -- Sport, corruption and white-collar 'criminality': crimes of the powerful (1) -- Governing young people and communities through sport? -- Modes of security, governance and surveillance in sport -- Cultural criminology, sport and transgression -- Sport and social harms - Qatar and World Cup 2022 in focus: crimes of the powerful (2) -- Conclusion: (even) further towards a critical criminology of sport.